Health experiences of children and young people who migrate – Opportunities for health education. (February 2019) - Spencer, Grace; Smith, Melody; Thompson, Jill; Fairbrother, Hannah; Hoare, Karen; Fouché, Christa; Curtis, Penny
Research on migration and health is gaining significant ground, with a focus on the adverse physical and mental health outcomes experienced by migrants. The health-related experiences of children and young people who migrate, however, are relatively absent, with children's migration and health status often conflated with that of their parents. The omission of children's own perspectives limits knowledge about how health is understood and experienced by child migrants, including the identification of best ways to support their health. Drawing on the empirical literature on child migrants and health from the World Health Organization's (WHO) Western Pacific Region, we adopt a critical perspective to examine how the research to date supports a particular way of understanding and investigating the health of children and young people who migrate. Specifically, we highlight how a dominant focus on parents' migration status, (negative) health outcomes and patterns of risk behaviours limits, rather than aids, the understanding of migrant children's health. In doing so, we illustrate how much of the evidence base upholds Westernised biomedical notions of health and privileges the use of particular methodologies to assess health outcomes and reduce health risks. These preferences, in turn, shape the subsequent range of 'appropriate' forms of health education for, rather than with, children. We conclude by drawing on some exceptions and consider the opportunities these provide for developing health education in line with children's own understandings of health – crucially underscoring the importance migrant children and young people attach to the more social aspects of their health and migration experiences.